Efficacy of metalaxyl formulations in controlling downy mildew of pearl millet and their residues under arid climate - GUPTA*, G. K. (Indian Phytopathology, 2002)
A field experiment was conducted to evaluate the various formulations of metalaxyl for the control of downy mildew and its residue in pearl millet under two different rainy seasons in arid climate of Rajasthan. Seed treatment with Apron (4.2 g a.i. klfl seed) + two Ridonil MZ 72 WP sprays (2.88 kg a.i, ha') at 20 and 40 days after sowing (d.a.s.), seed treatment with Apron (2.1 g a.i. klfl seed) + two sprays of Ridomil MZ 72 WP (1.44 kg a.i. ha') and Apron seed treatment (4.2 g a.i. klfl seed) + one Ridoniil MZ 72 WP spray (2.88 kg a.i. ha-I)were found effective in controlling the disease, where disease incidences were 0.9, 3.2 and 3.5%, espectively as compared to check (49.4%) at 70 d.a.s. Apron (4.2 g a.i, klfl seed) was superior than @ 2.1 g.a.i. klfl seed. Spray of Ridomil MZ 72 WP alone was more effective than seed treatment with Apron. Efficacy of metalaxyl was found higher in the season less conducive to downy mildew development. Harvest time residues of metalaxyl and of mancozeb were either nil or in trace in soil, grain and straw of pearl millet.